2019
DOI: 10.1109/access.2019.2893056
|View full text |Cite
|
Sign up to set email alerts
|

Lightweight Quantum Encryption for Secure Transmission of Power Data in Smart Grid

Abstract: The rise of the smart grid, which applies the Internet and smart metering technologies to the power system, results in massive, heterogeneous power data and a large number of attacks on the smart grid and causes great threats to the confidentiality and integrity of the power data. At the same time, with the development of quantum information, it is possible to use quantum cryptography to protect data transmission. Aiming at the problem of data security transmission in smart grid, this paper proposes a lightwei… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
21
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 48 publications
(21 citation statements)
references
References 22 publications
0
21
0
Order By: Relevance
“…Bretas et al [25] gave a proof of how parameter errors spread out to the measurements functions and pointed analytical method for cyber-physical security in smart grid as a malicious data attack to detect. Wang et al [26] proposed a data framing attack detection algorithm based on support vector machine, and proved that the proposed algorithm in this paper has [8,13,16,17] encryption and decryption high resource consumption high security [9] data mining unable to address specific security protections easy to discover new attack modes [10] private transmission control protocol not many scenarios high security [11] access control low efficiency high security [12] heuristic planning failed to protect grid information system high grid physical security [14,15] security domain division low efficiency high security [18] intrusion detection unable to withstand unknown attacks easy to discover new attack modes [19] game theory difficult to understand provides quantitative analysis capabilities for data security a good performance on the IEEE benchmark. Ayad et al [27] used recurrent neural networks to detect false data injection attacks.…”
Section: Data Attack For Smart Gridmentioning
confidence: 68%
See 1 more Smart Citation
“…Bretas et al [25] gave a proof of how parameter errors spread out to the measurements functions and pointed analytical method for cyber-physical security in smart grid as a malicious data attack to detect. Wang et al [26] proposed a data framing attack detection algorithm based on support vector machine, and proved that the proposed algorithm in this paper has [8,13,16,17] encryption and decryption high resource consumption high security [9] data mining unable to address specific security protections easy to discover new attack modes [10] private transmission control protocol not many scenarios high security [11] access control low efficiency high security [12] heuristic planning failed to protect grid information system high grid physical security [14,15] security domain division low efficiency high security [18] intrusion detection unable to withstand unknown attacks easy to discover new attack modes [19] game theory difficult to understand provides quantitative analysis capabilities for data security a good performance on the IEEE benchmark. Ayad et al [27] used recurrent neural networks to detect false data injection attacks.…”
Section: Data Attack For Smart Gridmentioning
confidence: 68%
“…301-309 This is an open access article published by the IET under the Creative Commons Attribution-NonCommercial-NoDerivs License (http://creativecommons.org/licenses/by-nc-nd/3.0/) research work in the field of data security protection for smart grid. Li et al [8] proposed a lightweight transmission scheme for power data security in smart grid. Zhu et al [9] indicated that the existing wireless communication in smart grid could make users' data easily be leaked.…”
Section: Introductionmentioning
confidence: 99%
“…In this section, as summarized in Table IV, we have selectively surveyed only authentication schemes that involve quantum channels. The work [71] has proposed a method to authenticate both the sender and receiver nodes, during the key distribution process of an EB protocol. The authentication is achieved through the verification of an additional authentication key which is kept at a trusted key server.…”
Section: Authentication Of Qkd Nodesmentioning
confidence: 99%
“…The joint consideration of both node authentication and secret key distribution in [71] is also addressed by [73], but in a different way. In [73], BB84 is first used to generate a secret key s i between the key server and the ith nodes in the communication network.…”
Section: Authentication Of Qkd Nodesmentioning
confidence: 99%
“…These lightweight features offer better performance in terms of energy as compared to the traditional cryptographic algorithms. To transmit smart grid power data securely, Yuancheng Li et al [281] proposed a lightweight quantum encryption algorithm. The scheme consists of key distribution, authentication, and data transmission process.…”
Section: ) Lightweight Cryptographymentioning
confidence: 99%